Evidence from Human and Animal Studies: Pathological Roles of CD8+ T Cells in Autoimmune Peripheral Neuropathies - Yang, Mu; Peyret, Corentin; Shi, Xiang Qun; Siron, Nicolas; Jang, Jeong Ho; Wu, Sonia; Fournier, Sylvie; Zhang, Ji (Frontiers in Immunology, 2015)
Autoimmune peripheral neuropathies such as Guillain Barre Syndrome (GBS) and chronic inflammatory demyelinating polyneuropathy (CIDP) affect millions of people worldwide. Despite significant advances in understanding the pathology, the molecular and cellular mechanisms of immune-mediated neuropathies remain elusive. T lymphocytes definitely play an important role in disease pathogenesis and CD4+ T cells have been the main area of research for decades. This is partly due to the fact that the most frequent animal model to study autoimmune peripheral neuropathy is experimental allergic neuritis (EAN). As it is induced commonly by immunization with peripheral nerve proteins, EAN is driven mainly by CD4+ T cells. However, similarly to what has been reported for patients suffering from multiple sclerosis, a significant body of evidence indicate that CD8+ T cells may play a pathogenic role in GBS and CIDP disease development and/or progression. Here, we summarize clinical studies pertaining to the presence and potential role of CD8+ T cells in autoimmune peripheral neuropathy. We also discuss the findings from our most recent studies using a transgenic mouse line (L31 mice) in which the T cell co-stimulator molecule B7.2 (CD86) is constitutively expressed in antigen presenting cells of the nervous tissues. L31 mice spontaneously develop peripheral neuropathy, and CD8+ T cells are found accumulating in peripheral nerves of symptomatic animals. Interestingly, depletion of CD4+ T cells accelerates disease onset and increases disease prevalence. Finally, we point out some unanswered questions for future research to dissect the critical roles of CD8+ T cells in autoimmune peripheral neuropathies.